A mix of apple pomace polysaccharide improves mitochondrial function and reduces oxidative stress in the liver of high‐fat diet‐induced obese mice. Issue 3 (31st January 2017) - Chen, Lei; Liu, Lei; Li, Caixia; Hu, ChengLi; Su, Fan; Liu, Run; Zeng, Mengqi; Zhao, Daina; Liu, Jiankang; Guo, Yurong; Long, Jiangang
Abstract : Apple pomace polysaccharides (APPs) are one of the major bioactive compounds found in the locally abundant "Qinguan" apple pomace. It is reported that APP can reduce oxidative stress, promote mitochondrial functions, and thereby inhibit high‐fat diet‐induced obesity and insulin resistance. Collected data indicates that APP could be an effective nutrient for preventing hepatic metabolic disorder. Abstract : Scope: Apple pomace polysaccharides (APP), a free radical scavenger, is one of the major compounds derived from apple pomace. However, whether APP has beneficial effects on metabolic disorders is still unknown. Methods and results: In the present study, water‐soluble APP was isolated from the pomace of the locally abundant "Qinguan" apple and chemically characterized. Then, APP was orally administrated to high‐fat diet (HFD)‐induced obese mice. We found that APP significantly reduced HFD‐induced body weight gain and ameliorated HFD‐induced hepatic metabolic disorders and oxidative stress. In a palmitate‐loaded HepG2 cell model, APP protected the cells from palmitate‐induced insulin resistance and loss of viability by suppressing mitochondrial reactive oxygen species and rescuing mitochondrial respiratory function. Conclusion: Our work suggests that APP, a promising bioactive food component, successfully improved obesity‐associated hepatic metabolic disorder, most likely though the activation of hepatic mitochondrial function and the suppression of mitochondria oxidative stress.